Exposure to predicted precipitation patterns decreases population size and alters community structure of cyanobacteria in biological soil crusts from the Chihuahuan Desert - Fernandes, Vanessa M. C.; Machado de Lima, Nathali Maria [UNESP]; Roush, Daniel; Rudgers, Jennifer; Collins, Scott L.; Garcia-Pichel, Ferran (Wiley-Blackwell, 2018)
Cyanobacteria typically colonize the surface of arid soils, building biological soil crust (biocrusts) that provide a variety of ecosystem benefits, ranging from fertilization to stabilization against erosion. We investigated how future scenarios in precipitation anticipated for the Northern Chihuahuan Desert affected abundance and composition of biocrust cyanobacteria in two grassland ecosystems. Scenarios included a decrease in precipitation and a delay of monsoon rainfall. After three years, both treatments negatively affected cyanobacteria, although the effects of monsoon delay were milder than those of decreased precipitation. Mature biocrusts in black grama grassland suffered severe losses in cyanobacterial biomass and diversity, but compositionally simpler biocrusts in blue grama-dominated grassland maintained biomass, only suffering diversity losses. This could be partially explained by the differential sensitivity of cyanobacterial taxa: nitrogen-fixing Scytonema spp. were the most sensitive, followed by phylotypes in the Microcoleus steenstrupii complex. Microcoleus vaginatus was the least affected in all cases, but is known to be very sensitive to warming. We predict that altered precipitation will tend to prevent biocrusts from reaching successional maturity, selecting for M. vaginatus over competing M. steenstrupii, among pioneer biocrust-formers. A shift towards heat-sensitive M. vaginatus could ultimately destabilize biocrusts when precipitation changes are combined with global warming.